Peran Bumdes Mbule SIO Terhadap Peningkatan Pendapatan Asli Desa Lekunik Kecamatan Lobalain Kabupaten Rote Ndao - Marthen Lona (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
This research aims to analyze the role of the Mbule Sio Village-Owned Enterprise (BUMdes) in Lekunik Village, Lobalain District, Rote Ndao Regency in increasing the Original Income of Lekunik Village. The type of research carried out is qualitative research using qualitative descriptive methods in the form of case studies. Data collection techniques were carried out using observation, questionnaires and interviews as well as reviewing other documents. Next, the data was analyzed to obtain an overview of the role of BUMDes Mbule Sio in increasing Village Original Income (PADes). The research results show that BUMDes Mbule Sio has played a positive role in increasing the Original Income of Lekunik Village during 2019 and 2020. This is shown by the amount of net profit contribution given by BUMdes Mbule Sio to PADes Lekunik Village, namely in 2019 amounting to IDR 730,350 and For 2020, the net profit contribution to Village Original Income is IDR 854,950 or an increase of 17.06%. Judging from the size of the BUMDes contribution to the PADes of Lekunik village, it should be acknowledged that the amount is still relatively small due to the various obstacles faced by BUMDes Mbule Sio in carrying out its business activities.